Influence of Problem Posing Learning Model with Support Software Camtasia on The Ability of Understanding Student’s Mathematical - Setiyani Setiyani; Sri Sumarwati; Mohd Hasril Amiruddin; Yusuf Himawan (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
This study aims to find out how students 'activities in using the problem posing learning model with the help of Camtasia software affect to the ability of Mathematical Understanding, find out how the influence of the problem posing learning model with the help of Camtasia software on the Students' Mathematical Understanding Ability, to determine student responses in learning using problem posing learning models with the help of Camtasia software. The research is experimental method with the population all students of grade X in 7th State Senior High School Cirebon City. The respondent selected used purposive sampling technique. By comparing pretest (before being given treatment) with posttest (already given treatment). Data collection techniques using tests, observations and questionnaires. Data analysis used observation analysis, normality test, regression test and t test. The results of this study indicate that the learning outcomes of students whose learning using Camtasia-based video media is better than students with conventional learning models.